1970
DOI: 10.3329/bvet.v25i1.4616
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of some medicinal plant products of indigenous origin

Abstract: Chemical compositions of leaves of neem (Azadirachta indica), sajna (Moringa oleifera), arjun (Terminalia arjuna), tulsi (Ocimum sanctum), turmeric (Curcuma longa); rhizomes of ginger (Zingiber officinale) and turmeric; fruits of amla (Emblica officinalis), haritaki (Terminalia chebula), bohera (Terminalia belerica) and bulbs of garlic (Allium sativum) of indigenous origin were determined. Proximate and mineral components [Calcium (Ca), Phosphorus (P), Sodium (Na), Potassium (K), Magnesium (Mg), Copper (Cu), Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Crude protein content of concentrate mixture was 19.00%. Theng Kouch et al (2003) observed 36.23% DM, 89.56% OM, 12.81% CP and 10.41% ash in jackfruit leaf which is almost similar to the study, Devendra (1982) found 30.00% DM, 22.20% CP and 4.40% ash in Leucaena leaves and Bhowmik et al (2008) Found 34.6% DM, 19.34% CP, 32.00 % ADF and 13.92% ash in neem leaves.…”
Section: Nutrient Compositionsupporting
confidence: 70%
“…Crude protein content of concentrate mixture was 19.00%. Theng Kouch et al (2003) observed 36.23% DM, 89.56% OM, 12.81% CP and 10.41% ash in jackfruit leaf which is almost similar to the study, Devendra (1982) found 30.00% DM, 22.20% CP and 4.40% ash in Leucaena leaves and Bhowmik et al (2008) Found 34.6% DM, 19.34% CP, 32.00 % ADF and 13.92% ash in neem leaves.…”
Section: Nutrient Compositionsupporting
confidence: 70%
“…Pudina (Mentha arvensis) used against digestive and vomiting. Tulsi leaves contained higher amount of Na, Cu and Zn (Bhowmik et al, 2008). From recent search valuable medicinal plant as Tulsi and Pudina are found endangered in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…(Azadirachta indica) is a useful conventional medicinal plant in Bangladesh. In all parts of the neem tree has some medicinal properties and is commercially exploitable for the development of medicines and industrial byproducts (Bhowmik et al, 2008). These plants are used as digestive stimulants, antidiarrhoic, antiseptic, antiinflammatory, antiparasitic and appetite stimulants in human beings as well as animals.The antimicrobial activity of extracts of neem leaves against such microorganisms as Staphylococcus spp, Streptococcus spp, Pseudomonas spp and Escherichia coli, and some fungal strains have been reported many researchers (Valarmathy et al, 2010).…”
Section: Neemmentioning
confidence: 99%